Association Between Weight Misperception and Some Mental Health-Related Characteristics in Korean Adolescents - Lee, Keon Hui (Neuropsychiatr Dis Treat, 2020)
BACKGROUND: Obesity in adolescents is associated with their mental as well as physical health. Adolescents tend to have negative or distorted perceptions about their body weight; however, the effects of such weight misperception on mental health remain unclear. This study investigated the association between weight misperception and mental health in Korean adolescents. METHODS: The analysis was based on the Korea Youth Risk Behavior web-based survey 2017 dataset, which included data from 62,276 middle and high school students at 800 schools throughout Korea. The students were divided into three groups according to whether they overestimated their body weight, underestimated it, or had no misperception. The mental health characteristics of the overestimation and no misperception groups were compared through multiple logistic regression analysis. RESULTS: Based on their body mass index, male adolescents were more likely to be overweight than female adolescents (p < 0.001) and less likely to have weight misperception. The female adolescents were more likely to overestimate their body weight and less likely to underestimate it (p < 0.001). The male adolescents and female adolescents who overestimated their body weight had significantly lower levels of subjective happiness than their peers had and were more likely to experience subjective stress, sadness/despair, suicidal ideation, and suicide planning. Compared with their peers who have no misperception, male adolescents with overestimation were less likely to drink alcohol (odds ratio [OR], 0.903) or smoke (OR, 0.871), whereas female adolescents with overestimation were more likely to drink alcohol (OR, 1.107) and smoke (OR, 1.130). CONCLUSION: Male and female adolescents who overestimated their body weight experienced more psychological problems. Thus, interventions to assist adolescents to gain realistic weight perception may be beneficial. Particularly, more attention needs to be given to female adolescents, who are more likely to overestimate their body weight compared with their male counterparts.